2017
DOI: 10.1007/s00766-017-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Goal-oriented requirements engineering: an extended systematic mapping study

Abstract: Over the last two decades, much attention has been paid to the area of goal-oriented requirements engineering (GORE), where goals are used as a useful conceptualization to elicit, model, and analyze requirements, capturing alternatives and conflicts. Goal modeling has been adapted and applied to many sub-topics within requirements engineering (RE) and beyond, such as agent orientation, aspect orientation, business intelligence, model-driven development, and security. Despite extensive efforts in this field, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 51 publications
1
68
0
1
Order By: Relevance
“…Several authors [5,9,11,12,14,16,18,30] reported requirements engineering methodologies for BI projects, which are primarily focused on DW and DM aspects. The available BI requirement approaches are broadly classified into various categories such as data mining [1], use cases [3,31], model driven [32], data driven [5,42], Goal oriented [12,33,34,43], and business process oriented [35,36,37].…”
Section: Methodsmentioning
confidence: 99%
“…Several authors [5,9,11,12,14,16,18,30] reported requirements engineering methodologies for BI projects, which are primarily focused on DW and DM aspects. The available BI requirement approaches are broadly classified into various categories such as data mining [1], use cases [3,31], model driven [32], data driven [5,42], Goal oriented [12,33,34,43], and business process oriented [35,36,37].…”
Section: Methodsmentioning
confidence: 99%
“…The former is more intuitive and generally associated with services to be provided to customers while the latter is related to quality, sometimes performance or resources required for service, and also related to external demands such as safety requirements, performance, safety, aspects, etc. Here, a requirement is a necessary condition to reach a given goal in a specific application domain (Horkoff et al, 2017). Therefore, since in the direct approach nonfunctional requirements are usually neglected or fail to compose a complete set, goal-oriented methods are becoming an interesting alternative to large systems.…”
Section: Gore:goal Oriented Requirements Methodsmentioning
confidence: 99%
“…A modelagem orientada a objetivo (goal-oriented model) é eficaz para capturar as interações e compensações de requisitos dentro de um contexto e por esse motivo tem sido aplicada de forma mais ampla para promover o estado de áreas como adaptação de software, segurança, conformidade legal e business intelligence, entre outras áreas (Horkoff et al, 2017).…”
Section: A Modelagem Orientada a Objetivos E O Istarunclassified